Kajian Komprehensif Perkembangan Penelitian Nanoteknologi melalui Pendekatan Bibliometrik - Ni Putu Tiara Kusumadewi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Nanotechnology is a nanoscale technological innovation (1–1000 nm) that has been widely used in the pharmaceutical and medical fields, especially as a more effective and specific drug delivery system. This technology is able to increase the bioavailability of drugs, reduce side effects, and increase the efficacy of therapy. This study aims to explore the development and thematic focus of studies on nanotechnology published in PubMed during the period 2015–2025, using bibliometric methods and data visualization through the VOSviewer software. Data is collected through the Publish or Perish application with the keywords